Popular Sovereignty in the Algorithmic Era: Reassessing the meaning of the Will of The People in the Digital Public Space - Asep Sapsudin (Global Writing Academica Researching & Publishing, 2024)
The development of artificial intelligence (AI) and commercial algorithmic systems has transformed the landscape of the digital public sphere, resulting in distortions in the process of public opinion formation. This study aims to reassess the meaning of popular sovereignty when the digital public sphere is controlled by the interests of global technology corporations through surveillance capitalism. Using a juridical-normative legal research method with a conceptual and comparative approach, this study examines the mechanics of algorithms in manipulating citizens' free will. The results show that algorithmic control systematically reduces the originality of the people's will to mere quantitative data through the formation of filter bubbles, echo chambers, and psychographic manipulation techniques in the form of political micro-targeting. This phenomenon triggers acute sociopolitical polarization, undermines the legitimacy of substantial democracy, and gives rise to new threats of techno-authoritarianism. This study concludes that the concept of popular sovereignty in the digital era requires fundamental redefinition through the recognition of the right to cognitive liberty and digital sovereignty. The state must intervene legally at the upstream level by enforcing the principle of algorithmic transparency, regular algorithm audits, limiting micro-targeting, and optimizing the Personal Data Protection Law (PDP Law). Indonesia can adopt international standards such as the European Union's Digital Services Act and AI Act to restore ultimate power to the digitally independent people, rather than the control of private platforms' algorithmic code.